Donor site morbidity of composite free flaps in head and neck surgery: a systematic review of the prospective literature. Issue 9 (September 2021) - Russell, J.; Pateman, K.; Batstone, M.
Abstract: Composite free flaps represent the cornerstone for the repair of osseous defects in the head and neck. For many patients, there are often multiple defect-suitable donor sites that may be utilised as part of the reconstructive process. Therefore, to optimise patient outcomes, an evidence-based approach to donor site selection is required to maximise quality of life and long-term functionality. A systematic review of the literature was conducted in accordance with PRISMA guidelines to evaluate the evidence for donor site selection based on minimising the associated donor site morbidity and optimising patient functionality postoperative. The fibula is associated with the greatest potential risk for wound healing complications. Fibula and scapula harvest has the potential to have a significant impact on physical performance. The iliac crest is most favourable in terms of aesthetic scar healing outcomes. Overall, however, the quality and quantity of evidence for all donor sites is limited. Each site is associated with specific complications and morbidity, of which the surgeon and patient must both be aware. Whilst a cross-sectional informed opinion of the likely advantages/disadvantages of one donor site over another can thus be made, there are few head-to-head studies available that directly compare donor sites.